2019
DOI: 10.9734/jeai/2019/v38i130291
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Aqueous Extract of Castor Bean (Ricinus communis) to Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae)

Abstract: The objective of this study was to evaluate the insecticidal effect of aqueous extract of castor bean (Ricinus communis) cake for the control of Maconellicoccus hirsutus. The toxicity tests were performed in the laboratory. Subsequently lethal concentrations 50 and 90% (LC50and LC90, respectively) were estimated. Tween80® + distilled water was used as surfactants and solvent respectively. The assay was performed in petri dishes containing a Coffea canephora leaf disc. The spraying was carried out in Torre de P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Averages followed by the same letter, uppercase on the line and lowercase on the column, do not differ by the F and Scott-Knott test, respectively, at the level of 5% probability The higher percentages of mortality were observed in the form of indirect application could be attributed to the fact that the cocoa leaf discs were completely immersed in the solutions, which could act on individuals in different ways, either by ingestion (through the digestive system, before penetration into plant tissue) or by contact, crossing the integument and through the airways, which would facilitate the intoxication process, since M. hirsutus has a thin layer of powdery secretion around its body that protects it in the case of spraying [2,16]. However, some authors argue that the action by contact is faster than the mode of action by ingestion.…”
Section: Resultsmentioning
confidence: 99%
“…Averages followed by the same letter, uppercase on the line and lowercase on the column, do not differ by the F and Scott-Knott test, respectively, at the level of 5% probability The higher percentages of mortality were observed in the form of indirect application could be attributed to the fact that the cocoa leaf discs were completely immersed in the solutions, which could act on individuals in different ways, either by ingestion (through the digestive system, before penetration into plant tissue) or by contact, crossing the integument and through the airways, which would facilitate the intoxication process, since M. hirsutus has a thin layer of powdery secretion around its body that protects it in the case of spraying [2,16]. However, some authors argue that the action by contact is faster than the mode of action by ingestion.…”
Section: Resultsmentioning
confidence: 99%
“…new resistant populations, cause mortality of natural enemies present in the environment, the intoxication of the surrounding fauna, and pollution of water bodies [9] . As an alternative to synthetic chemical control, research related to the use of extracts and substances obtained from plants has demonstrated satisfactory effectiveness in pest control [10,9,11] . Among the plants with acaricidal effects, peppers, belonging to the Solanaceae family, have a variety of alkaloid compounds and saturated or unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%